(untitled) (Journal of University of Babylon for Engineering Sciences, 2024)
Modern, promising and environmentally friendly nanomaterials was used as adsorbent material, [AL2O3 Nanoparticles, loaded Aloe vera Gum]. It is a natural material that is secreted from the (Aloe vera plant) based nanocomposites using sol-gel method to increase the surface area to Phosphate removal. Selectors within a range are dose of (Al2O3/AG) nanoparticles (20-100 mg), initial ion concentration (Ci) 3.7-10.7 mg/L. pH for solution 3,4,5,7, and 9, contact time 5-100 minutes, wavelength of light (yellow, white, red, green, blue, and sunlight), and magnetic field (MF) 300-500 mTesla. Batch experiments were conducted using The Hanna Phosphate High-Range Checker. Results showed the best dose 60 mg, pH 5, wavelength red, contact time 100 min and Ci of PO4-3 at 7.6 mg/L. It is found that the Langmuir adsorption model fairly fits the experimental data; while the pseudo-second-order kinetic model fits the adsorption. The adsorption capacity is increased with the decrease of initial concentration of the pollutant (phosphate) and is directly proportional to the dose of Al2O3/AG nanocomposites adsorbent. The best conditions obtained using Al2O3/AG is compared with fly ash and Al2O3 NPs. The surface area of Al2O3/AG nanocomposites was recorded as 124.255 m2. g-1. The best operating condition that gives the highest removal was used to test AL2O3 NPs and fly ash. It is proved that AL2O3/AG gives higher removal than that of AL2O3 NPs and fly ash.